1982
DOI: 10.1029/jb087ib10p08581
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer in a fault‐controlled geothermal reservoir charged at constant pressure

Abstract: A two~dimensional mathematical model of a fault controlled geothermal reservoir has been developed. Heated lighter water, rising in the fault, is assumed to charge a reservoir which, in turn, is overlain by a thin impermeable, thermally conducting cap rock. The mass flow rate or the pressure associated with the charging process at the fault inlet is unknown and can only be estimated. Thus, in this paper, the pressure in the fault at the bottom of the reservoir is assumed to be prescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…For this reason we assume that the pressure gradient is orthogonal to the fault plane and that the fluids in the fault core move perpendicularly to the fault plane with a geometrically averaged velocity v. Moreover, to allow for an analytical approach we assume that fluid motion does not have a component in the direction of the fault plane. More sophisticated 2D numerical solutions for the fluid-and thermo-dynamical problem have been developed by Williams and Narasimhan (1989) for the study of the San Andreas fault and by Goyal and Narasimhan (1982) for the case of a fault-controlled geothermal reservoir charged at a constant pressure (1982). However these equations do not incorporate the effect of rate-, state-and temperature-dependent friction laws.…”
Section: The Temperature Evolution In the Case Of A Constant Fluid Vementioning
confidence: 99%
“…For this reason we assume that the pressure gradient is orthogonal to the fault plane and that the fluids in the fault core move perpendicularly to the fault plane with a geometrically averaged velocity v. Moreover, to allow for an analytical approach we assume that fluid motion does not have a component in the direction of the fault plane. More sophisticated 2D numerical solutions for the fluid-and thermo-dynamical problem have been developed by Williams and Narasimhan (1989) for the study of the San Andreas fault and by Goyal and Narasimhan (1982) for the case of a fault-controlled geothermal reservoir charged at a constant pressure (1982). However these equations do not incorporate the effect of rate-, state-and temperature-dependent friction laws.…”
Section: The Temperature Evolution In the Case Of A Constant Fluid Vementioning
confidence: 99%
“…Numerical studies by Bodvarsson and Tsang (1981) have shown that this assumption is quite reasonable.…”
Section: Rock2mentioning
confidence: 99%
“…Goyal and Narasimhan (1981) have recently used a similar model for a constant pressure charging of a fault controlled geothermal reserovoir.…”
Section: General Backgroundmentioning
confidence: 99%
“…The solution techniques involve boundary layer theory, numerical methods and a combination of perturbation methods. Kassoy and Zebib (1978) use the same basic solution techniques as Goyal and Narasimhan (1982), however, they consider only a fault zone. Pritchett and Garg (1979) studied a fault-charged reservoir by numerically simulating mass and energy transport in the aquifer, while neglecting bedrock heat losses.…”
Section: Fault-charged Modelmentioning
confidence: 99%
“…Several authors have studied the temperature distribution in fault-charged geothermal reservoirs, including Goyal and Narasimhan (1982), Goyal and Kassoy (1981).…”
Section: Fault-charged Modelmentioning
confidence: 99%